An Approach for Pre-Lithiation of Li1+xNi0.5Mn1.5O4 Cathodes Mitigating Active Lithium Loss. Issue 15 (18th October 2019) - Betz, Johannes; Nowak, Laura; Winter, Martin; Placke, Tobias; Schmuch, Richard
Abstract : A major challenge for longer life lithium ion batteries is the irreversible loss of active lithium during the first charge/discharge cycles, which consequently reduces the practical energy density in cells without lithium ion excess. This degradation mechanism is especially detrimental for high-capacity anodes with low first cycle Coulombic efficiency. The present study aims for overcoming this challenge by pre-lithiating the high-voltage spinel LiNi0.5 Mn1.5 O4 (LNMO) positive electrode material with a simple and easily scalable chemical process via stirring LNMO particles with Li metal in boiling pentanol. The subsequent structural and electrochemical analysis proves the electrochemical accessibility of the "extra" lithium and long-term cycling stability. Charging/discharging the material in LNMO || graphite (C) and LNMO || silicon/carbon (Si/C) cells demonstrates positive effects on discharge capacity, energy and capacity retention. Furthermore, the additional active lithium is used to increase the specific capacity of the cells by including the lower potential region of LNMO through application of a lower cell cutoff voltage of 2.4 V. Comparing "standard" LNMO || C with pre-lithiated LNMO || Si/C cells (both charged/discharged at standard cutoff voltages of 3.0 and 4.95 V), improvements in specific energy of >21% can be identified.